PENERAPAN MODEL PROJECT BASED LEARNING DENGAN ROLE PLAY UNTUK MENINGKATKAN KEMAMPUAN BERBICARA BAHASA JEPANG - Nurlaili, Iva (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2022)
Abstract: Japanese is one of the foreign language subjects in high school which has a level of difficulty for students when studying it. In learning, it was still found that students' Japanese speaking skills were still low. Therefore, this research was conducted with the aim of finding out how to improve students' speaking skills by implementing the Project Based Learning model with role play in class XI MIPA 1 SMA Progresf Bumi Shalawat. The subjects of this research were 25 Phase F students of SMA Progresif Bumi Shalawat. This Classroom Action Research was carried out in 2 learning cycles with 2 meetings each. Based on observations in cycle I, the percentage of completeness in students' speaking skills was 56% and the percentage of completeness in cycle II was 100%. This means that students' speaking ability has increased by 44%, noting that even though there was still 1 person who got a score according to the KKM, namely 75. The most visible thing is that when students work on a project to create speaking conversations, students are given the freedom to create conversations so that participants Students can develop speaking skills by playing roles with groups. So it can be concluded that the project based learning model with role play can improve the ability to speak Japanese on the material of Gakkou no Seikatsu in class XI students at SMA Progresif Bumi Shalawat.